“AM I CREATIVE ENOUGH OR PERFECTLY CHARMING?” Gender Comparison of How Millennials Represent themselves on Instagram - Sosiawan, Edwi Arief; Wibowo, Rudi (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2021)
Photos uploaded by the millennial generation are the process of re-purposing the means of photography in the form of self-representation as a way to construct their identity. This self-identity construction process also involves gender roles related facts that demonstrate various behaviors in the social media use. Photos posted as self-representation are not only getting a normative or supportive response in the caption as a comment or like, but also bringing up cases and problems. This article figures out the gender comparison in the self-identity construction of the millennial generation in social media Instagram. The netnography (virtual ethnography) method used to interpret the phenomenon of the daily behavior of the millennial generation on Instagram. Primary data derived from hypertext interactions with the millennial generation of Instagram users. The findings point that the male millennial prefer to present themselves as an intimate and friendly person who is close to the family in daily life. They are also more oriented towards presenting their preferences and hobbies by visualizing symbols related to them, such as highlighting creativity with tools used as photo and video cameras. While the female millennial tend to dislike daily show because it is considered a private matter. However, they like to show their identity through fashion or clothing known as OOTD, highlight their creative products, and more focus on themselves. To cite this article (7th APA style):Sosiawan, E. A. & Wibowo, R. (2021). "Am I creative enough or perfectly charming?" Gender comparison of how millennials represent themselves on Instagram. Journal Communication Spectrum: Capturing New Perspectives in Communication, 11(1), 64-73. http://dx.doi.org/10.36782/jcs.v1i1.2151